2014
DOI: 10.1128/iai.00861-13
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Epithelial Cell-Derived S100 Alarmins Induced by Candida albicans via Pattern Recognition Receptor Interactions Are Sufficient but Not Necessary for the Acute Neutrophil Response during Experimental Vaginal Candidiasis

Abstract: dVulvovaginal candidiasis (VVC), caused by Candida albicans, affects women worldwide. Animal and clinical studies suggest that the immunopathogenic inflammatory condition of VVC is initiated by S100 alarmins in response to C. albicans, which stimulate polymorphonuclear neutrophil (PMN) migration to the vagina. The purpose of this study was to extend previous in vitro data and determine the requirement for the alarmin S100A8 in the PMN response and to evaluate pattern recognition receptors (PRRs) that initiate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 56 publications
4
63
3
Order By: Relevance
“…Although CP can be toxic to C. albicans in vitro, its efficacy as an antifungal agent in vivo may vary depending on the host niche. For example, CP Ϫ/Ϫ mice are substantially more susceptible to C. albicans infection of the lung (26), but not to vaginal candidiasis, in spite of abundant neutrophil recruitment to the vaginal tissue (78). If anything, the opposite was observed: the fungal burden was decreased in vaginal tissues of CP Ϫ/Ϫ mice (78), and we observed that the same is true during fungal invasion of the kidney.…”
Section: Discussionsupporting
confidence: 57%
“…Although CP can be toxic to C. albicans in vitro, its efficacy as an antifungal agent in vivo may vary depending on the host niche. For example, CP Ϫ/Ϫ mice are substantially more susceptible to C. albicans infection of the lung (26), but not to vaginal candidiasis, in spite of abundant neutrophil recruitment to the vaginal tissue (78). If anything, the opposite was observed: the fungal burden was decreased in vaginal tissues of CP Ϫ/Ϫ mice (78), and we observed that the same is true during fungal invasion of the kidney.…”
Section: Discussionsupporting
confidence: 57%
“…Expression of the gene coding for S100A8 (S100a8), a calciumbinding protein with important functions in antifungal defense and danger responses and strongly induced during C. albicans infection, was almost completely absent during infection with Candidalysin deletion strains (Fig. 5J) (21,22). Similarly, the gene encoding serum amyloid A3 (Saa3), an inducible acute-phase apolipoprotein capable of recruiting immune cells to inflammatory sites, was similarly increased in a Candidalysin-dependent fashion (Fig.…”
Section: Figmentioning
confidence: 82%
“…86 Recently it was shown that S100A8 alarmin is sufficient, but not necessary, to induce PMN migration during experimental vaginal candidiasis. 87 …”
Section: Prrs Of Epithelial Cellsmentioning
confidence: 99%